Державна політика України щодо протидії політичній корупції під час військового стану - Давітян Вемір Суренович (My University, 2023)
Кваліфікаційну роботу присвячено вивченню теоретичних засад дослідження державної політики України щодо протидії корупції. В межах дослідження проведений аналіз та з’ясовано особливості державної політики України щодо протидії корупції під час військового стану. А також окреслені проблеми ефективної боротьби проти корупції в Україні в умовах воєнного стану та шляхи їх вирішення. Об’єктом дослідження є суспільні відносини щодо формування державної політики з протидії і запобігання корупції. Предметом дослідження є державна політика України із запобігання політичній корупції під час військового стану. Ключові слова: корупція, запобігання корупції, антикорупційне законодавство, публічні закупівлі, воєнний стан.

The qualification work is devoted to the study of the theoretical foundations of the study of the state policy of Ukraine in the fight against corruption. Within the framework of the study, the analysis was carried out and the specifics of the state policy of Ukraine regarding combating corruption during martial law were clarified. Also, the problems of effective fight against corruption in Ukraine under martial law and the ways to solve them are outlined. The object of the study is public relations in relation to the formation of state policy to combat and prevent corruption. The subject of the study is the state policy of Ukraine to prevent political corruption during martial law. Keywords: corruption, prevention of corruption, anti-corruption legislation, public procurement, martial law.
State policy of Ukraine regarding countering political corruption during martial law